IoT based Water Parameter Testing in Linear Topology - Nemade, Bhushan; Shah, Deven (2020 10th International Conference on Cloud Computing, Data Science & Engineering (Confluence), 2020)
Water resources are becoming inadequate and will turn out to be the restrictive factor for sustainable development in the near future in rural and urban areas. Due to development in communication technology, smart solutions for water quality monitoring and management are gaining importance. Water impurities monitoring in terms of its physical and chemical properties is important in most of the water reservoirs. Existing water quality monitoring system are not able to adapt abrupt changes on time at long distance. Also, it is time-consuming process and tough task to obtain real time water parameter for analysis purpose. To Address these problems, New algorithm LTGM is proposed for assessment of water quality parameters and faulty sensor node detection by adapting Internet of Things, wireless sensor network and communication standards. Thus, proposed system is intended for real time applications for detecting water impurities by placing the sensors nodes in linear topology. Proposed system also classifies water quality into four classes for parameters such as temperature, PH, turbidity, TDS etc. collected from each sensor node and also detects the water impurities at every sensor node.